A fluorescence in situ hybridization‐based screen allows rapid detection of adverse cytogenetic alterations in patients with acute myeloid leukemia. Issue 8 (19th May 2017) - Sandhöfer, Nadine; Metzeler, Klaus H.; Kakadia, Purvi M.; Pasalic, Zlatana; Hiddemann, Wolfgang; Neusser, Michaela; Steinlein, Ortrud; Fiegl, Michael; Subklewe, Marion; Spiekermann, Karsten; Bohlander, Stefan K.; Schneider, Stephanie; et al.
Abstract: In adult acute myeloid leukemia (AML), the karyotype of the leukemic cell is among the strongest prognostic factors. The Medical Research Council (MRC) and the European LeukemiaNet (ELN) classifications distinguish between favorable, intermediate and adverse cytogenetic risk patients who differ in their treatment response and overall survival. Conventional cytogenetic analyses are a mandatory component of AML diagnostics but they are time‐consuming; therefore, therapeutic decisions in elderly patients are often delayed. We investigated whether a screening approach using a panel of seven fluorescence in situ hybridization (FISH) probes would allow rapid identification of adverse chromosomal changes. In a cohort of 334 AML patients, our targeted FISH screening approach identified 80% of adverse risk AML patients with a specificity of 99%. Incorporating FISH screening into diagnostic workup has the potential to accelerate risk stratification and treatment selection, particularly in older patients. This approach may allow therapeutic decisions more quickly, which benefits both patients and physicians and might save costs.